Metodología para la elaboración de mapas acústicos como herramienta de gestión de ruido urbano en la ciudad de machala - Berrezueta Berrezueta, Juliana Elizabeth (2017)
The present investigation was based on the noise pollution existing in the city of Machala, considered for the study a specific area of the downtown area of the city which is comprised between schools, in order to propose a methodology for the elaboration of acoustic maps specifically for the control and monitoring of sound levels as an urban noise management tool. The project is based on a feasible type of research, based on the diagnostic parameters, the theoretical approach, the analysis and the execution of the project, using two types of sources, both documentary and field. This research includes an advanced development divided into different stages, group of techniques and instrumentation, starting from the collection of data determined specifically by the interviews conducted and acoustic surveys in situ, direct observation, collection of sources of documentary research, use of sound instruments, elaboration of the acoustic maps and the respective analysis of the results that allow to know the acoustic environmental conditions currently in the study area. In the development of research work, definitions of the subject were formulated through various sources of documentary research, including noise, its types and the effect it causes on people's health; sound pressure and their respective levels; decibels and their unit of measure; classes, weighting curves, calibration and steps for the use of the sound level meter; isophonic curves and ranges of hearing threshold and pain threshold; noise maps and their processing methodology, ArcGIS and interpolation methods; tables obtained from TULSMA and UNE ISO 1996-2: 1997. A total of 21 acoustic probes were performed throughout the study area using an analog RadioShack sound level meter, complying with the parameters established in the Unified Text of Environmental Legislation (TULSMA), published in the official registry in November 2015, both for use correct sound level metering, noise mapping, Critical Affect Points (PCA) selection and the measurement range that was chosen in this case by the 15-second Method (Leq 15s). The surveys were conducted in order to obtain knowledge of the sound environment in the study area, the percentage of residents who know about the effects of acoustic pollution on their health and the basis for the Environmental Authorities in the area noise. The area chosen for the study shows a high degree of noise pollution determined by the average of the data recorded in each PCA obtained through the soundings. The acoustic maps, elaborated in the ArcGIS Software applying two of the methods of interpolation that allows us to weight measured values to determine a prediction of the location of a value without measurements, the methods used were the IDW and Kriging, they show the sound behavior of the area of study and the representation of the ranges of noise levels with their respective color.